The Characterization of Intracellular and Extracellular Biomineralization Induced by Synechocystis sp. PCC6803 Cultured under Low Mg/Ca Ratios Conditions. Issue 4 (21st April 2017) - Han, Zuozhen; Zhao, Yanyang; Yan, Huaxiao; Zhao, Hui; Han, Mei; Sun, Bin; Meng, Ruirui; Zhuang, Dingxiang; Li, Dan; Gao, Wenjing; Du, Shiyun; Wang, Xiaoai; et al.
ABSTRACT: In order to simulate the precipitation process of microbial limestone at the offshore of the ancient ocean, different calcites induced by Synechocystis sp . PCC6803 in culture media with low Mg/Ca ratios (0.01 M Ca 2+, Mg/Ca = 0, 0.2, 0.4, 0.6) were investigated, and the characteristics of intracellular and extracellular biomineralization were described. Carbonic anhydrase activity of Synechocystis sp . PCC6803 in different culture medium was further detected. The ultrathin slices of Synechocystis sp . PCC6803 cells were analyzed by transmission electron microscope (TEM) and selected area electron diffraction (SAED). Then the precipitates were analyzed by polarizing microscope, scanning electron microscope (SEM), X-ray diffraction (XRD) and energy dispersive spectrometer (EDS). The results showed that the biomineralization precipitates of Synechocystis sp . PCC6803 under low Mg/Ca ratios were mainly calcites with different morphologies. The CA accelerated the pivotal rate limiting step of the calcite precipitation. It was also found that the morphology, microstructure, particle size, preferred orientation, crystallinity and cell volume of calcites changed gradually with the increasing Mg 2+ concentrations. What is more important, it was found that Synechocystis sp . PCC6803 had the ability of intracellular biomineralization without crystal structure. The intracellular biomineralization product could be divided into two types. This study can provide some useful information for further understanding the characteristics and mechanisms of biomineralization and even the diagenetic environment research of microbial limestone.